Kinetics of blisters growth in a deformed α-Fe at low-energy deuterium plasma exposure - Nikitin, A.V.; Tolstolutskaya, G.D.; Kopanets, I.E.; Karpov, S.A.; Ruzhytskiy, V.V. (Вопросы атомной науки и техники, 2018)
The results of the study of surface topography evolution and the features of deuterium interaction with α-Fe
under glow discharge 1 keV deuterium ions bombardment at Troom up to ion fluence of 3.4·10²⁴ D/m²
are presented.
At a threshold irradiation dose the formation of blisters with dimensions ranging from 0.01 to 1 mm is observed.
The extent of blistering development is determined by ability of hydrogen to penetrate to the depths exceeding the
ions stopping range of 1 keV hydrogen by orders of magnitude and by the density, location depth and mutual
arrangement of fissures in the preliminarily deformed material. Представлено результати дослідження еволюції топографії поверхні та особливостей взаємодії дейтерію
з α-Fe при бомбардуванні іонами тліючого розряду з енергією 1 кеВ при Tкімн. до дози 3,4·10²⁴ D/м². При
пороговій дозі опромінення спостерігається утворення блістерів з розмірами від 0,01 до 1 мм. Ступінь
розвитку блістерінга визначається здатністю водню проникати на глибини, що перевищують на порядки
пробіг іонів водню з енергією 1 кеВ, а також щільністю, глибиною і взаємним розташуванням тріщин у
попередньо деформованому матеріалі. Представлены результаты исследования эволюции топографии поверхности и особенностей
взаимодействия дейтерия с α-Fe при бомбардировке ионами тлеющего разряда с энергией 1 кэВ при Tкомн. до
дозы 3,4·10²⁴ D/м²
. При пороговой дозе облучения наблюдается образование блистеров с размерами от 0,01
до 1 мм. Степень развития блистеринга определяется способностью водорода проникать на глубины,
превышающие на порядки пробег ионов водорода с энергией 1 кэВ, а также плотностью, глубиной и
взаимным расположением трещин в предварительно деформированном материале.